Further extension of the improved hyperbolic function method with application to general Sawada–Kotera equation of fifth-order, The 3D potential-YTSF equation and (mKdV) equation. - Wafaa M. Taha (Tikrit Journal of Pure Science)
In this study, a new improved hyperbolic function method is applied for the first time. The proposed method used to calculate more general exact solutions for the general Sawada–Kotera equation of fifth-order, 3D potential-YTSF equation and modified Korteweg-de Vries (mKdV) equation. The obtained results show that the improved hyperbolic function method provides and easy and fast solution when used with mathematical software such as Maple. The finding also indicates that the proposed method helps in understanding the physical structures of the problem.